MODEL LAYANAN PUBLIK RAMAH DIFABEL INISIATIF MEMBANGUN KOTA INKLUSI: Diffabble-Friendly Public Service Model Building Initiatives the City of Inclusion - Rahmawati, Rahmawati; Putranto, Heru Adi (Pencerah Publik, 2023)
Disability is a complex issue at all levels of society. Disabilities include people with physical and psychological deficiencies in society. So the mention of people with disabilities can be more familiar by calling them disabled. With the diffable predicate, people can easily divide their social strata with ’normal people’ rather than ’disabled/disabled people’. The purpose of this research is to find ideas and theoretical foundations that can be used to define "inclusive cities." Because definitions alone are not enough, this article will also examine indicators of inclusive cities. This study uses qualitative research. Based on the theoretical studies conducted, the authors argue that there are four indicators of an inclusive city: (i) the participation of persons with disabilities; (ii) there are efforts to fulfill the rights of persons with disabilities; (iii) guaranteed accessibility; and (iv) the inclusive attitude of the city residents.